FACTORS FOR INACCESSIBILITY OF ANTENATAL CARE BY WOMEN IN SINDH - Yousuf, Farhana; Haider, Gulfareen; Shaikh, Raheela Bilal (Journal of Ayub Medical College Abbottabad, 2010)
Background: Antenatal care is important for pregnant women. By good antenatal care many complications of pregnancy can be prevented and lives can be saved. This study was carried out to find out the reasons of not utilising antenatal care, knowledge about dangerous signs and symptoms of pregnancy, and diet in women receiving and not receiving antenatal care. Methods: This descriptive study was conducted at Department of Obstetrics and Gynaecology, Liaquat University Hospital, Hyderabad Pakistan from February 2007 to October 2007. A total of 134 women who came for delivery were included in the study. Out of these, 71 women had received antenatal care while 63 did not receive antenatal care. After taking informed consent, women were interviewed regarding demographic data, reason of not utilising antenatal care, knowledge about diet and dangerous signs and symptoms of pregnancy. Results: Twenty-eight (44.44%) women did not receive antenatal care because the facility was far away from home, 10 (15.87%) said that transport was not available. Tetanus toxoid coverage was higher among women who received antenatal care (p<0.0001). Women who received antenatal care were more aware of the dangerous signs and symptoms of pregnancy than women who did not receive antenatal care. Conclusion: Most common reason of not utilising antenatal care was that facility was far away from there home. Women who received antenatal care were not anaemic and had received tetnus toxoid vaccination. They knew more about diet and dangerous sign and symptoms of pregnancy than women who had not received antenatal care. Keywords: Antenatal care, women, anaemic, rural, pregnancy, facility, safe motherhood, Sindh